STUDIES ON LARVAL HAEMOLYMPH PROTEIN LEVELS OF SELECTED RACES OF THE SILKWORM, BOMBYX MORI L. UNDER TEMPERATE CLIMATES OF KASHMIR - AWQUIB SABHAT; A. M. SOFI; M. A. MALIK; FIRDOSE AHMAD MALIK (The Bioscan, 2011)
Changes in the levels of protein in the haemolymph of eleven selected races of the silkworm, Bombyx mori L. viz., SH-6, SKAU-R-6, SKUAST-31, Dun6, Yakwei and CSR-5 (oval races) and NB4D2, SKAU-R-1, SKUAST-13, SKUAST-28, CSR-4 (constricted races), were investigated during 5th instar larval development in spring and summer season. The levels of total protein in the haemolymph, increased from first day of 5th instar till sixth day. From seventh day, the protein levels decreased significantly in all the races. Racial differences in the changes in the levels of protein in the haemolymph were observed in the larvae when reared during spring and summer season. The haemolymph proteins in spring season increased significantly from 41.34 to 66.79 mg/mL in SKAUR-6 followed by SH-6 (38.88-61.13 mg/mL), SKUAST-31 (41.07-60.17 mg/mL), Dun6 (39.66-58.13 mg/mL), CSR-5 (38.29-55.85 mg/mL) and Yakwei (35.80-54.93 mg/mL). However, during summer season, there was a significant decrease in the haemolymph protein levels in all the races. But, the order of decrease was significantly higher in Yakwei >CSR-5 > Dun6 >SKAU-R-6 >SH-6 >SKUAST-31. The present study revealed that the high temperature during summer induces specific changes in the metabolism (reversible thermal stress) that have different adaptive value in different races of the silkworm. Relatively higher increase in the protein levels in the haemolymph of SKAU-R-6, SKAU-R-1 and NB4D2 presumably provides protective cover to tissues against high temperature during summer. The absence of such a mechanism may be responsible for temperature susceptibility of the bivoltine races like Yakwei, CSR-5, SKUAST-13 and CSR-4.